1962
DOI: 10.1161/01.cir.25.3.522
|View full text |Cite
|
Sign up to set email alerts
|

The Antihypertensive Effects of Chlorthalidone

Abstract: Chlorthalidone administered in a single daily dose (200 mg. per day) produced a significantly greater hypotensive effect than chlorothiazide (250 mg. t.i.d.) and a greater, but not significantly different, response than hydrochlorothiazide (25 mg. t.i.d.). Reserpine (0.1 to 0.5 mg. per day) significantly augmented the hypotensive effect of chlorthalidone, but chlorthalidone given alone produced an effect equal to the combination of a benzothiazide with reserpine. Side effects characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…It was noted that urate excretion tended to be increased during the 6 h periods following diuretic administration when the drugs' activity and excretion were at a maximum (Branch et al, 1977;Davies et al, 1974) and decreased during the subsequent periods of sodium retention. These observations are in keeping with the suggestion that diuretic induced urate retention is fundamentally related to diminished extracellular fluid volume (Steele, 1971;Suki, Hull, Rector & Seldin, 1967) rather than competition between drug and urate for a common tubular secretory pathway (Bryant, Yu, Berger, Schvartz, Torosdag, Fletcher, Fertig, Schwartz & Quan, 1962;Olesen, Sigurd, Steiness & Leth, 1973). The similarity between the patterns of urate and sodium excretion observed in this study are consistent with the previously reported relationship between their excretions and the suggestion that mechanisms which adjust tubular sodium reabsorption may also alter urate excretion (Cannon, Svahn, & Demartini, 1970).…”
Section: Discussionsupporting
confidence: 92%
“…It was noted that urate excretion tended to be increased during the 6 h periods following diuretic administration when the drugs' activity and excretion were at a maximum (Branch et al, 1977;Davies et al, 1974) and decreased during the subsequent periods of sodium retention. These observations are in keeping with the suggestion that diuretic induced urate retention is fundamentally related to diminished extracellular fluid volume (Steele, 1971;Suki, Hull, Rector & Seldin, 1967) rather than competition between drug and urate for a common tubular secretory pathway (Bryant, Yu, Berger, Schvartz, Torosdag, Fletcher, Fertig, Schwartz & Quan, 1962;Olesen, Sigurd, Steiness & Leth, 1973). The similarity between the patterns of urate and sodium excretion observed in this study are consistent with the previously reported relationship between their excretions and the suggestion that mechanisms which adjust tubular sodium reabsorption may also alter urate excretion (Cannon, Svahn, & Demartini, 1970).…”
Section: Discussionsupporting
confidence: 92%
“…The drugs most commonly associated with FDE are antibiotics, analgesics, thiazide diuretics and anticonvulsants [4]. Chlorthalidone, a thiazidetype diuretic that inhibits distal convoluted tubule sodium and chloride resorption, is a commonly used oral antihypertensive [5,6]. Here by we are presenting a case of chlorthalidone induced FDE.…”
Section: Introductionmentioning
confidence: 97%
“…One of them, pargyline, has been promoted as an antihypertensive drug (Bryant et al 1963) but it is scarcely practicable to use it extensively for this purpose when other drugs with less troublesome side effects are available. Pargyline is sometimes worth trying in patients who are both hypertensive and depressed (Simpson and Waal-Manning, 1971) but cases of depression have been reported in patients taking it (Oates et al 1965).…”
Section: Blood Pressure Problems In Patients Onmentioning
confidence: 99%